Digital fundamentals with VHDL. - Floyd, Thomas L., 1939- (Upper Saddle River : Prentice Hall, 2003)
This text is an adaptation of Floyd's best-selling Digital Fundamentals-widely recognized as the authority in digital electronics texts-that also applies basic VHDL concepts to the description of logic circuits. It introduces digital logic concepts and functions in the same way as the original book, but with an emphasis on PLDs rather than fixed-function logic devices. Fundamental concepts of digital logic form the core of the book, while VHDL is presented as a tool for implementing the digital logic in programmable logic devices. Complete, up-to-date coverage, from the basic digital logic concepts to the latest in digital signal processing, is provided.
Keywords: VHDL (vhsic hardware description language).